Workload Risk Analysis of the Optimal Packing Division Using RWL, REBA, and OCRA Methods on Musculoskeletal Disorders - Irma Dwi Setyowati; Boy Isma Putra (Procedia of Engineering and Life Science, 2022)
Physical work and body posture will be related to the workload obtained, because it will affect production results. Based on the observations of 4 packing operators, there are problems with how they work, so there are some defective/failed to packs products, because some operators complain of fatigue, especially in the hands, back, and feet, and do not focus on one job. From material lifting, and packing processes to cleaning up failed products and products that fall from the conveyor. The methods used are the Recommended Weight Limit (RWL), Rapid Entire Body Assessment (REBA), and Occupational Repetitive Action (OCRA). can find out the level of risk category of each packing operator, and can improve posture/body position and workload carried out, with the aim of improving the workings of the riskiest operators in order to be optimal at work. The results of the study were operators 3 and 4 with higher working risk levels. The workload for operators 3 0.80 ± LI = did not cause any risk to the activity performed and the weight of the load lifted, resultant posture score 9 (very risky), right-handed activity 6.7 (medium risk), and left-handedness 11.9 (very risky). Whereas operator 4 obtained a workload yield of 1.14 li LI, which may increase the risk of complaints of waist pain and weight lifted beyond the standard, posture 6 (medium), right-hand activity 11.2 (high risk), and left hand 6.7 (medium risk).